An Exploratory Study on Secure Software Practices Among Software Practitioners in Malaysia - Mohamed, Shafinah Farvin Packeer; Baharom, Fauziah; Deraman, Aziz; Yahya, Jamaiah; Mohd, Haslina (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
Rapid growths of computers, mobile phones and Internet technology have created ways for irresponsible people to undertake computer crimes. Millions of users across the globe have fallen as victims to computer crimes, including Malaysia. It is due to current software environment which is more complex, distributed, keeps confidential data and easily exposed to malicious attacks. Consequently, secure software process is increasingly gaining much importance among software practitioners and researchers. However, even though its importance has been revealed, only few studies were conducted regarding its current practice in the software industry, especially in Malaysia. Thus, an exploratory study is conducted among software practitioners in Malaysia to study their experiences and practices on the secure software process in the real-world projects. This paper discusses the findings from the study, which involved 93 software practitioners. Structured questionnaire is utilized for data collection purpose whilst statistical methods such as frequency, mean, and cross tabulation are used for data analysis. Outcomes from this study reveal that software practitioners are becoming increasingly aware on the importance of secure software process, however, they lack of appropriate implementation of the practices.